2017
DOI: 10.3390/vaccines5010005
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Memory: A Dynamic View

Abstract: Long-term T cell-mediated protection depends upon the formation of a pool of memory cells to protect against future pathogen challenge. In this review we argue that looking at T cell memory from a dynamic viewpoint can help in understanding how memory populations are maintained following pathogen exposure or vaccination. For example, a dynamic view resolves the apparent paradox between the relatively short lifespans of individual memory cells and very long-lived immunological memory by focussing on the persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 60 publications
2
53
0
1
Order By: Relevance
“…They observed that dicentric lesions remained present for more than a decade in the naive T‐cell pool, and for less than a year in the memory T‐cell pool. Although the study was based on markers that are now considered insufficient to sort naive T cells, it was the first to demonstrate that in humans, immunological memory is maintained dynamically rather than by long‐lived cells …”
Section: Labeling Studies Consistently Show That Naive T Cells Live Mmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that dicentric lesions remained present for more than a decade in the naive T‐cell pool, and for less than a year in the memory T‐cell pool. Although the study was based on markers that are now considered insufficient to sort naive T cells, it was the first to demonstrate that in humans, immunological memory is maintained dynamically rather than by long‐lived cells …”
Section: Labeling Studies Consistently Show That Naive T Cells Live Mmentioning
confidence: 99%
“…Although the study was based on markers that are now considered insufficient to sort naive T cells, 26 it was the first to demonstrate that in humans, immunological memory is maintained dynamically rather than by long-lived cells. 27 We now know that some of these studies may have overestimated T-cell turnover rates because diurnal variation in deuterium availability was hardly taken into account. 12 Nevertheless, the relative naive and memory turnover rates within each study -which do not suffer from these problems -unequivocally show that memory T cells in the blood are shorter lived than their naive counterparts.…”
Section: Ab Eling S Tud Ie S Con S Is Tently S How That Naive T Cmentioning
confidence: 99%
See 1 more Smart Citation
“…27 An obligate intracellular microbe such as O. tsutsugamushi would need a combination of antibodies and cellmediated immunity working together to confer protective immunity. Generally, it is accepted that T-cell immunity memory is long lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Immune memory is previously considered as an exclusive property of T cells and B cells and defined as quicker and more robust responses to recurrent antigens [72]. However, accumulating evidence proved NK cell also have memory-like feature after certain modes of challenge including antigen-specific stimulation and antigen-independent activation.…”
Section: Generation Of Memory-like Natural Killer Cellsmentioning
confidence: 99%